Henoch–Schönlein Purpura Associated with Lung Cancer: When Paraneoplastic Manifestations Impede Oncological Management - Philippe, Éloïse (Case Reports Immunol, 2021)
BACKGROUND: Henoch–Schönlein purpura (HSP) is an uncommon syndrome that mostly occurs in children, in whom it is frequently triggered by infections. In contrast, HSP in adults is more frequently of neoplastic origin. Case Presentation. We report HSP associated with a locally advanced lung squamous cell carcinoma that was considered a paraneoplastic syndrome. Systemic corticosteroids were given because a kidney biopsy revealed active glomerulonephritis. Concomitant chemoradiotherapy achieved a partial response of the lung tumor. Consolidation immunotherapy (programmed death protein-1-ligand-1 (PD-L1) inhibitor) was cancelled because HSP is known to be an autoimmune vasculitis, and long-term corticosteroid therapy was pursued. CONCLUSION: Further prospective studies are needed to evaluate the effect of anti-PD-(L) 1 immunotherapies on autoimmune manifestations.